Anomalous Origin of Coronary Arteries from Opposite Situs and the Conundrum of Sudden Death Pathophysiology: Insights from Interventional Cardiology - Cocco N.; Gelfusa M. (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
An anomalous aortic origin of a coronary artery (AAOCA) from the opposite sinus, with an interarterial course, has been associated with an increased risk of myocardial ischemia and sudden death. The prevalence of coronary artery anomalies in patients undergoing coronary angiography ranges from 1% to 5% [1]. This variation depends on the population studied and the definitions used to categorize the anomalies. Their detection is crucial due to their potential to cause life-threatening events. As the exact pathophysiology of AAOCA is not well understood, the clinical management is also not well defined. With the increased use of non-invasive imaging, the diagnosis of AAOCA is increasing and the association of anomalous origin and atherosclerotic disease is becoming a more important topic. Several studies have been done to find a true “denominator” causing ischemia and sudden cardiac death (SCD). The pathophysiological mechanisms taken into account include ischemia caused by mechanical compression exerted on the artery tract with an abnormal course, its geometric alterations (including a slit-like ostium, acute take-off angle, and proximal narrowing) and histopathological changes in the vessel wall. This chapter is given as an example of a rare case of AAOCA chronic total occlusion (CTO). A 40-year-old Caucasian man was referred for invasive coronary angiography (ICA) due to typical chest pain and positive myocardial scintigraphy. ICA demonstrated CTO of an anomalous right coronary artery (ARCA) originating from the left side of the ascending aorta with an interarterial course. During the procedure, an unexpected rupture of the coronary artery occurred after dilatation with a small balloon at low pressure. The complication was an opportunity for food for thought. Coronary artery perforations are rare but life-threatening procedural complications that are usually caused by predisposing anatomical and procedural factors. Based on this complication, this study hypothesized that the arterial wall might be fragile due to pathological alterations, potentially contributing to the pathophysiology of coronary malignancy. Recent studies conducted on small samples have shown the presence of histopathological alterations (such as elastic fiber alterations, mural fibrosis, and smooth muscle disarray) in patients with anomalous aortic origin of a coronary artery [2]. However, further autopsy studies, including larger samples, are needed to understand the histopathological changes associated with coronary anomalies and an increased risk of SCD.